Diseases Related to Maternal Mortality in Wad Medani Obstetrics and Gynecology Teaching Hospital, Sudan (2011-2014) - Abdalla, Samira Mohammed; Fadol, Isam Omer (Gezira Journal of Economic and Social Sciences; Vol 5 No 2 (2014), 2014)
Worldwide an estimated 529,000 girl and woman die of pregnancy related causes each year about one every minute and many time that number suffer long term injuries and disabilities.  99% of all maternal death occurs in the developing world (WHO 2005). In Sudan many women's dies due to pregnancy related complications, and those who survive suffer from sever maternal morbidity. This study aimed to explore    the most common diseases related to maternal mortality in Sudan with references to Wad Medani Obstetrics and Gynecology Teaching Hospital during the period (2011-2014). The study used data collected from Wad Medani obstetrics and Gynecology Teaching Hospital annual reports for which data were completed and available include 245 cases. For data analysis the study used descriptive analytical methodology and Chi-square test.  The result revealed that the indirect causes of maternal deaths    responsible of 69.7% including, malaria, cancer, heart diseases, liver diseases and jaundice. While the direct cusses represent 30.3 of maternal death and this include Hemorrhage, bleeding poisoning, abortion and eclampsia. The study recommended that raising the awareness of women with the importance of follow up visit during pregnancy and after delivery. Also the study recommended that working to sustain malaria fighting program and intensify the effort in this regard.